2011
DOI: 10.1038/mt.2011.175
|View full text |Cite
|
Sign up to set email alerts
|

Co-operative Membrane Disruption Between Cell-penetrating Peptide and Cargo: Implications for the Therapeutic Use of the Bcl-2 Converter Peptide D-NuBCP-9-r8

Abstract: Delivering apoptosis inducing peptides to cells is an emerging area in cancer and molecular therapeutics. Here, we have identified an alternative mechanism of action for the proapoptotic chimeric peptide D-NuBCP-9-r8. Integral to D-NuBCP-9-r8 is the Nur-77-derived D-isoform sequence fsrslhsll that targets Bcl-2, and the cell-penetrating peptide (CPP) octaarginine (r8) that is required for intracellular delivery. We find that the N-terminal phenylalanine of fsrslhsll acts in synergy with the cell-penetrating mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…NuBCP-9 was linked to the D-Arg octamer r8 for intracellular delivery, a modification that has been reported to decrease selectivity by inducing BCL-2-independent cell killing involving membrane disruption (15). In the present work, delivery of NuBCP-9 into cancer cells by the polymeric NPs was achieved without the need for the R8 PTD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NuBCP-9 was linked to the D-Arg octamer r8 for intracellular delivery, a modification that has been reported to decrease selectivity by inducing BCL-2-independent cell killing involving membrane disruption (15). In the present work, delivery of NuBCP-9 into cancer cells by the polymeric NPs was achieved without the need for the R8 PTD.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of a certain CPP is of importance in that the CPP can in a cargo-dependent manner contribute to decreased serum stability, inefficient transit from the endosome to the cytosol and unanticipated toxicities (14). Indeed, for NuBCP-9, the cell-penetrating r8 used for intracellular delivery acts in synergy with the N-terminal phenylalanine of NuBCP-9 to cause membrane blebbing and cell necrosis that are independent of BCL-2 expression (15). These findings have supported the study of alternative CPPs for NuBCP-9 or other formulations that preclude the use of a CPP for intracellular delivery.…”
Section: Introductionmentioning
confidence: 99%
“…To test the effect of differing Bcl-2 status, further evaluation of new compounds was carried out in the human cancer cell lines KG1a (acute myelogenous leukaemia) and Jurkat (T cell leukaemia). The Jurkat cell line has previously been characterized as Bcl-2 negative by our group 17 and others, 18 unlike the Bcl-2 expressing KG1a cell line. 19 For studies on the leukaemic cells we used the CellTiter-Blue® viability assay, appropriate for endpoint determinations in these non-adherent cells.…”
Section: Treatmentmentioning
confidence: 99%
“…Rn induces non-specific cytotoxicity at high doses owing to its strong electrostatic interaction with the cell membrane. 14,23) Therefore, we considered the possibility that membrane integrity may be disturbed by short-time incubation of cells with the peptides. We measured cellular LDH levels after treatment with peptides to estimate membrane disruption.…”
Section: Fig 3 Uptake Efficiency Of Conjugates With Modified Hydropmentioning
confidence: 99%
“…12) In general, the uptake efficiency of oligoarginines (Rn), a kind of CPP, can be affected by the number of arginines comprising it. 14) Watkins et al have demonstrated that the uptake efficiency of octaarginine (R8) can be significantly enhanced by conjugation with NuBCP-9. 15) Therefore, the uptake characteristics of Rn comprising varying numbers of arginine could be altered by conjugation with NuBCP-9.…”
mentioning
confidence: 99%